EVALUATING THE EFFECTIVENESS OF ORAL HEALTH PROGRAM IN DENTALHOME AFTER 2 YEARS - Ralitsa Bogovska-Gigova; Rossitza Kabaktchieva (Peytchinski Publishing, 2022)
Introduction: The Dental Home is the ongoing relationship between the dentist and the patient, inclusive of all aspects of oral health care delivered in a comprehensive, continuously accessible, coordinated, and family-centered way. Dental practice, working on the principles of the Dental Home, increases the possibilities for caries prevention. Aim: The study aims to evaluate the effectiveness of our educational and motivational program created in the Dental Home for caries prevention for two years. Material and methods: The object of research and comparison are two groups of children - experimental and control. The experimental group includes 90 children who have two years of regular participation in our Dental Home and are theobject of our motivational and educational program. The control group are 30 childrenwho are visiting our Dental Home for the first time. We evaluated the effectiveness of preventive care led by the Dental Home by comparing the results in the two groups on the following criteria - dft - index, plaque index and level of caries risk. Our results confirmed that care in Dental Home reduces the spread of caries -85,56% of the children in our experimental group stayed caries-free, compared to 46.67% of the children in the control group.Significantly lower level of plaque accumulation was shown by the children for whom we created a Dental home. The number of children at high risk of caries development is significantly higher in the control group. Conclusion: A dental practice that works on the principles of the Dental Home has the potential to manage children's oral health.